SOSIALISASI LITERASI KEUANGAN DAN PRAKTIK INVESTASI SAHAM KEPADA GENERASI Z DI SMAN 1 WAINGAPU - Lusianus Heronimus Sinyo Kelen; Yulita Milla Pakereng; Vindya Donna Adindarena (Universitas Mataram, 2022)
Understanding of financial literacy in East Sumba Regency, East Nusa Tenggara (NTT) Province is a serious problem to be overcome. The results of previous research indicate the weakness of financial literacy in entrepreneurs in Waingapu City District, East Sumba Regency. To prevent and minimize this, the Community Service (PkM) implementation team conducted interactive socialization activities related to financial literacy and stock investment practices to Generation Z (in this case 15 students or students) at SMAN 1 Waingapu. This PkM aims to provide knowledge related to financial management and experience in investing in shares for generation Z. The selection of Generation Z as the target for PkM aims to introduce financial management and stock investment as investment products as early as possible. Activities carried out related to the implementation of PkM are financial literacy socialization and stock investment practices. The socialization was attended by students from SMAN 1 Waingapu who were accompanied by teachers. In this activity, students discussed with presenters related to financial literacy, then after the socialization ended the students were accompanied by the PkM team to practice stock investment using one of the financial technologies (fintech), namely Magic. As a result, students already have an account and make an investment of IDR 100,000 in the account that has been created. Then these activities ended with an evaluation to assess the stock development of the students. Community Service (PkM) related to the socialization of financial literacy, and stock investment practices to generation z (students) at SMAN 1 Waingapu was carried out well, where students gained knowledge related to financial management (in terms of financial literacy) as well as experience in make stock investments.